2013
DOI: 10.1007/978-1-62703-317-6_8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Mesenchymal Stem Cells from Human Bone and Long-Term Cultivation Under Physiologic Oxygen Conditions

Abstract: Bone-derived stroma cells contain a rare subpopulation, which exhibits enhanced stemness characteristics. Therefore, this particular cell type is often attributed the mesenchymal stem cell (MSC). Due to their high proliferation potential, multipotential differentiation capacity, and immunosuppressive properties, MSCs are now widely appreciated for cell therapeutic applications in a multitude of clinical aspects. In line with this, maintenance of MSC stemness during isolation and culture expansion is considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Recently, hypoxia has been widely explored to determine the effects on stem cell differentiation (Zhang et al, 2002;Klepsch et al, 2013). A previous study reported varying results for this analysis (Shav-Tal et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, hypoxia has been widely explored to determine the effects on stem cell differentiation (Zhang et al, 2002;Klepsch et al, 2013). A previous study reported varying results for this analysis (Shav-Tal et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MSCs represent a very suitable model for risk assessment as their response to radiation has been widely studied . Nanodiamond concentrations of 0.02, 0.2, 1, or 2 mg mL −1 were added to proliferating cells and incubated for either 24 or 72 h to assess cell viability (Figure a,b) . Only at the very high concentration of 2 mg mL −1 significantly increased death rates were revealed after 72 h. Note that an ND suspension of this concentration would have a specific activity of about 6 kBq mL −1 , assuming NDs were doped with 32 P as described above.…”
Section: In Vivo and Toxicity Testing Of 32p‐labeled Nanodiamondsmentioning
confidence: 99%
“…Human bone marrow-derived mesenchymal stem cells (MSC) were isolated, characterized, differentiated, and expanded as described previously [15]. The procedure yielded also good results when applied to isolate sheep cells.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to applying the explanted cells in animal experiments the primary ovine bone marrow-derived MSC were evaluated in culture. The cells revealed a spindle-like morphology with long processes and showed indistinguishable cell proliferation and colony formation when cultivated at 3% or 20% O 2 , yet exhibited slower rates when compared to human bone marrow-derived MSC [15, 16]. Colony formation was determined by seeding cells in 58 cm 2 cell culture dishes at a density of 10 cells/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation